A pilot, prospective, randomized trial of video versus direct laryngoscopy for paramedic endotracheal intubation. (May 2017) - Ducharme, Scott; Kramer, Brandon; Gelbart, David; Colleran, Caroline; Risavi, Brian; Carlson, Jestin N.
Abstract: Background: Prehospital intubation poses several unique challenges. Video assisted laryngoscopy has been shown to help increase intubation success in the hospital setting; however, little prospective data have examined video assisted laryngoscopy in traditional ground ambulance agencies. Methods: We performed a randomized, cross-over, non-blinded trial in ground ambulances comparing first attempt success and overall intubation success between video assisted laryngoscopy using the King Video Laryngoscope (KVL) and direct laryngoscopy (DL). We collected patient and provider demographics along with intubation details. Success rates were compared on a per-protocol and an intention-to-treat analysis. Results: Over 34 months, a total of 82 intubations were performed with 42 DL and 40 KVL based on the intention-to-treat analysis. First attempt success (28/42, 66.7% vs 25/40, 62.5%, p = 0.69) and overall success (34/42, 81% vs 29/40, 72.5%, p = 0.37) were similar between DL and KVL. Cormack-Lehane view and percentage of glottic opening were similar between devices. These results were consistent in the per-protocol analysis. Conclusions: In our study utilizing two ground EMS agencies, video assisted laryngoscopy with the KVL had similar first attempt success rates to direct laryngoscopy.